Trajetória histórica da Implantação do Sistema Único de Saúde (SUS) no município de Tarumã SP - Carricondo, Maria Paula Palma (2005)
The present work is a historical documental research that presents the trajectory of the municipal district of Tarumã in the adhesion of the Unified Health System. The history of the municipal district is described since its emancipation until the year 2003 for the construction of the health management of Tarumã. The Unified Health System can be considered one of the greatest social achievements of the country under the Constitution of 1988 and summed up by organizational and ethical beginnings, governed by a legal outline and standardizations. The Operating Standards provide to the local managers more autonomy for the administrative and financial management, but the increased accountability for installment of services places the municipal district in the aspect of uncertainties. Tarumã was emancipated in 1990 and it is considered a small municipal district as part of the 40% in the country. It comes prioritizing actions of Primary Health Care with the implantation of the Family Health Program in 1994 as it was also happened the adhesion to the national level, inserting the context of the strengthening of SUS and its beginnings, and characterizing a process of decentralization with the political and administrative decentralization of the section.